Tirzepatida como tratamiento de la obesidad en pacientes con o sin Diabetes tipo 2. - Freire Quisnancela, Willian Styben (2024)
Obesity has become one of the most significant public health challenges globally. Consequently, it has affected millions of people and profoundly impacted the health and quality of life of those affected. Its association with metabolic diseases, such as type 2 diabetes, and its contribution to the decrease in life expectancy reinforce the need for innovative therapeutic alternatives. Thus, tripeptide emerges as a promising option for the management of obesity. It was vital to evaluate the efficacy of Tirzepatide in people with obesity, both with type 2 diabetes and in non-diabetic patients, by a systematic review in recognized databases such as SciELO, PubMed, and Scopus. It is a descriptive, cross-sectional, and retrospective design with a qualitative and documentary approach. It included articles and studies published in the last five years, prioritizing meta-analyses and randomized clinical trials that analyzed the efficacy of Tirzepatide in this context. The results revealed that weekly administration of this drug shows a significant reduction in body weight in a dose-dependent manner and offers additional benefits in glycemic control, improving HbA1c levels in patients with type 2 diabetes without increasing the risk of major cardiovascular events. This therapy, approved by the FDA, is a safe and effective option since it significantly advances patients' quality of life and complies with cardiovascular safety standards.